Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/path.4485
|View full text |Cite
|
Sign up to set email alerts
|

AGE ‐modified basement membrane cooperates with Endo180 to promote epithelial cell invasiveness and decrease prostate cancer survival

Abstract: Biomechanical strain imposed by age-related thickening of the basal lamina and augmented tissue stiffness in the prostate gland coincides with increased cancer risk. Here we hypothesized that the structural alterations in the basal lamina associated with age can induce mechanotransduction pathways in prostate epithelial cells (PECs) to promote invasiveness and cancer progression. To demonstrate this, we developed a 3D model of PEC acini in which thickening and stiffening of basal lamina matrix was induced by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
67
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 42 publications
0
67
0
Order By: Relevance
“…Endo180 and CD147 have both been correlated with low levels of E-cadherin in tumor tissue, and both are under the transcriptional regulation of the core EMT trigger TGFb (7,8,19,20). In an aligned study, we have demonstrated that the stiff microenvironment associated with advanced glycation endproduct accumulation and collagen crosslinking of the basement membrane in the prostate gland is sufficient to activate an EMTlike phenotype in PEC acini by forcing the relocalization of Endo180 into endosomes and initiating an Endo180-dependent contractile signaling cascade that promotes cell invasion (21). Indeed, ECM stiffness has been identified as a regulator that can release matricellular TGFb in a number of pathologies (22).…”
Section: Discussionmentioning
confidence: 87%
“…Endo180 and CD147 have both been correlated with low levels of E-cadherin in tumor tissue, and both are under the transcriptional regulation of the core EMT trigger TGFb (7,8,19,20). In an aligned study, we have demonstrated that the stiff microenvironment associated with advanced glycation endproduct accumulation and collagen crosslinking of the basement membrane in the prostate gland is sufficient to activate an EMTlike phenotype in PEC acini by forcing the relocalization of Endo180 into endosomes and initiating an Endo180-dependent contractile signaling cascade that promotes cell invasion (21). Indeed, ECM stiffness has been identified as a regulator that can release matricellular TGFb in a number of pathologies (22).…”
Section: Discussionmentioning
confidence: 87%
“…5. Monitor acinar morphology in growing cultures using brightfield microscopy 13 . Note: After 3 days in culture individual cells will form a cluster of >3 cells and after 1 week prostate gland acini with a diameter of ~50 µm will be observed.…”
Section: D Culture Of Prostate Gland Acini On Native and Stiff Rbmmentioning
confidence: 99%
“…These acini also have the characteristics of highly organized PECs with apical-to-basal polarity and a visible luminal space 13,20 .…”
Section: D Prostate Acini Cultured On Stiff Rbmmentioning
confidence: 99%
See 2 more Smart Citations